Determining the Language Measurements in a Turkish-Persian Bilingual Child Suspected of Language Impairment: A Case Report - Galavizh Karimi Javan; Mahsa Mehdizadeh Behtash; Nahid Jalilehvand; Amirsalar Tozihi (Function and Disability Journal)
Background and Objectives: Bilingual children may be misdiagnosed with language impairment or, language impairment may not be diagnosed in these children due to postponing in diagnosing language problems after learning the second language. Determining a bilingual child’s language score includes assessment in both languages. The present study aims to report the language measurement scores in a Turkish-Persian bilingual child. Case Presentation: The language sample of an eight-and-a-half-year-old Turkish-Persian sequential bilingual boy with suspected language impairment was analyzed in both languages. For the syntactic domain, the measures of the mean length terminal-unit (MLTU), the number of grammatical errors per terminal-unit (NETU), the mean length of communication unit (MLCU), and for the semantic domain, the measure of a number of total words (NTW), the number of different words (NDW), and type-token ratio were used. Two variables of the age and duration of exposure to the second language were obtained. The age of exposure to the Persian language was 67 months and the duration of exposure was 33 months. Conclusion: The results demonstrated that the child’s performance is better in the Persian language than the Turkish in all measures except the number of grammatical NETU. This result can be justified according to the linguistic richness and duration of the child’s exposure. Finally, it is suggested to pay attention to the child’s language performance in each of his languages as well as his linguistic environment in diagnosing the Turkish-Persian bilingual children’s language impairment.